(untitled) (Unizik Journal of Chemical and Environmental Engineering, 2026)
The feedstock-dependent heterogeneity of lignin remains a major limitation in its rational design for interfacial applications, particularly as renewable oilfield demulsifier precursors. Although organosolv extraction and oxidative modification of lignin are widely reported, systematic cross-biomass evaluation under identical oxidative conditions remains largely unexplored, limiting the ability to decouple intrinsic biomass effects from reaction-driven transformations and constraining predictive materials design. In this study, lignins were extracted from rice husk (RH), sawdust (SD), and empty palm bunch (EPB) via an organic-acid organosolv process and subsequently oxidized using in-situ generated peracetic acid to engineer surface polarity and functionality. Structural evolution was characterized using FTIR, SEM, EDX, and TGA. FTIR analysis revealed consistent enhancement of carbonyl stretching (around 1740– 1715 cm−1) following oxidation, confirming oxygen incorporation while preserving aromatic backbone integrity ( 1600– 1510 cm−1). SEM demonstrated oxidation-induced disruption of supramolecular packing, producing fractured morphologies indicative of increased surface accessibility. EDX confirmed biomass-specific inorganic signatures, with RH lignin exhibiting pronounced silica retention, whereas SD and EPB contained comparatively lower mineral content. TGA profiles showed broad lignin degradation behavior, with residual mass strongly correlated to mineral burden. Importantly, oxidative structural reconfiguration was systematically governed by biomass origin, with SD lignin exhibiting the most pronounced functionalization, RH lignin showing mineral-induced heterogeneity, and EPB displaying intermediate transformation behavior. These findings establish biomass origin as a predictive design parameter in oxidative lignin engineering and provide mechanistic insight relevant to the future development of lignin- derived green materials for interfacial and surface-active applications.